2018
DOI: 10.18805/ijar.b-3565
|View full text |Cite
|
Sign up to set email alerts
|

Greater potentiality of sperm membrane bound fertility associated antigen to withstand oxidative stress ensuing improved sperm function of cryopreserved bull spermatozoa

Abstract: Fertility associated antigen (FAA) are more abundant in semen of bulls with high fertility. The objective was to investigate relationship of FAA, either membrane bound and/or in seminal plasma, with that of markers of oxidative stress, mitochondrial activity and acrosome integrity of live cells, in cryopreserved spermatozoa. Grouping of bulls was done by electrophoretic profiling of proteins from seminal plasma (SP), and sperm membrane (SM), based on presence/absence of the FAA in SP and/or SM or both. Group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It has been reported that these dead and moribund spermatozoa further deteriorate the functionality of their contemporaneous live cells [30]. Thus, the generation of ROS forms a vicious circle of self-generation and spermatozoal death; the greater the number of dead sperm, the greater the oxidative stress, which develops more cryoinjuries [31]. Previous studies from our laboratory have also reported a reduction in post-thaw sperm motility with the elevation of oxidative stress markers like malondialdehyde [32,33] and ROS [34,35].…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that these dead and moribund spermatozoa further deteriorate the functionality of their contemporaneous live cells [30]. Thus, the generation of ROS forms a vicious circle of self-generation and spermatozoal death; the greater the number of dead sperm, the greater the oxidative stress, which develops more cryoinjuries [31]. Previous studies from our laboratory have also reported a reduction in post-thaw sperm motility with the elevation of oxidative stress markers like malondialdehyde [32,33] and ROS [34,35].…”
Section: Discussionmentioning
confidence: 84%
“…The bovine seminal plasma proteins (BSPs) represent the major portion of bovine seminal plasma with three major heparin binding acidic proteins secreted by seminal vesicles which are BSP‐A1/A2 (also known as PDC‐109), BSP‐A3 and BSP‐30‐kDa amongst which PDC‐109 was found to mainly associated with cholesterol efflux from sperm membrane, binding with oviductal membrane as well as a role in induction of sperm capacitation and acrosome reaction (reviewed by Srivastava et al, 2013). In another studies, Pande et al (2018; 2019) concluded that presence of FAA on the sperm membrane was related to greater protection against oxidative stress as well as better freezability ensuing improved acrosome intact live‐sperm cells with functional mitochondria which could have a direct implication on the fertility. Therefore, these types of fertility markers could be used in prior selection of male animals before their induction in the breeding programmes.…”
Section: Male Fertility/infertility Evaluationmentioning
confidence: 99%
“…The exact reasons for the decreased sperm motility after cryopreservation remain unclear. It is assumed that they may be associated with oxidative stress and the resulting imbalance between the reactive oxygen species (ROS) formed and the activity of antioxidant defense systems (Agarwal et al, 2006;Pande et al, 2019). In addition, disorders may occur due to differences in the content of substances in the seminal plasma that ensure the normal functioning of spermatozoa such as L-carnitine (Nery et al, 2020).…”
Section: Introductionmentioning
confidence: 99%